Um embrião de laboratório de Pedagogia: as classes integrais do Colégio Estadual do Paraná no contexto das inovações pedagógicas no ensino secundário (1960-1967) - Sergio Roberto Chaves Junior (2017)
This study investigates the Classes Integrais do Colégio Estadual do Paraná (CEP), a proposal for pedagogical innovation in secondary education developed in the 1960s, with the entry of the first two high school classes and the 1967 school year, when the initiative ended. It seeks to analyze the singularities of the experience developed in this traditional institution of Paraná in the set of other initiatives of national range that went by the denomination of Classes Experimentais. The motivation to implement Classes Integrais arose from the need to solvedaily problems of CEP related to high rates of school failures and dropouts, resulting in the development of a curriculum adapted to the conditions of the students and the demands of a "democratic society in a growing phase of industrialization, urbanization and constantlychanging because of the influx of new scientific discoveries. Training investments were based on a "spirit of a full-time education", taking into account the following dimensions: physical education, intellectual, artistic, moral, sexual, religious formation, social education, and democracy for both work and leisure. The experimentalist conduct from the late 1950s contributed to the development of a set of curricular and methodological modifications, from which the following features stand out: expansion of full-time activities; simplification and flexibility of the programs of the subjects, adoption of active teaching methods;interrelationship of subjects; the study of the environment; out-of-class activities; personalized monitoring of students; changes in learning verification; teachers meetings and periodic meetings with the students' parents. It is part of the specificity of the Classes Integrais the place occupied by the Physical Education subject, due to the importance given to the students body dimension. In this subject, studies and methodological experiments were carried out even before the implementation of pedagogical innovation, and with the beginningof the Classes Integrais, it is possible to say that the intersection of two projects characterized by experimentalist conduct occurred, finding in that context the possible conditions for its achievement.